DETERMINASI KUALITAS AIR BUDIDAYA IKAN MENGGUNAKAN METODE INDEKS PENCEMARAN di SMART FISHERIES VILLAGE PANEMBANGAN - Ilma Azizah Arviani; Khothoh Syuraikhanah; Purnama Sukardi; Muslih Muslih; Dewi Wisudyanti Budi Hastuti; Nuning Vita Hidayati (JURNAL PERIKANAN DAN KELAUTAN, 2023)
Banyumas is one of the areas with the largest aquaculture center. One of the cultivation techniques applied is the cultivation of the Minapadi system. Panembangan, Banyumas which has been designated as a Smart Fisheries Village (SFV) is one of the developing areas for this system, with tilapia as a commodity. However, in developing it, several efforts are needed to maintain the physico-chemical quality of water as fish habitat. Therefore, it is necessary to analyze the physico-chemical quality of the water and the pollution status of the waters in the cultivation area. This study aims to determine the conformity between the quality standards and the condition of the physico-chemical parameters of water and its pollution status at the Panembangan SFV. Sampling was carried out at 10 predetermined points and carried out in September and October, 2022 with the parameters analyzed namely temperature, Dissolved Oxygen (DO), pH, nitrate, phosphate, heavy metals Cadmium (Cd), Chromium (Cr) and Lead (Pb). Data were analyzed using the Pollution Index (IP) method. Based on the analysis results, Mina Padi is included in the criteria for good waters in September and slightly polluted in October. Thus, further efforts are needed to maintain and reduce the status of water pollution in the Mina Padi Panembangan area so that the fish that are cultivated can grow optimally.